Análise espacial da distribuição das mulheres ocupadas nas famílias rurais no Sul do Brasil: uma perspectiva do gênero - Caumo, Alessandra Juliana (2012)
It was observed the spatial occurrence distribution of occupied women on rural families in Southern Brazil. This study showed another point of view about occupied women from Space Data Exploratory Analysis (AEDE). In the familiar agriculture the gender relations are most often, due to the work division imposed by the activity performed by the family members, and, in special the woman, her work is considered merely a help . This kind of analysis helps in a certain way, important changes in Brazil to be known and, mainly, in Southern Brazil in the distribution of occupied women. In this task was used the variable of occupied woman as the main one, but compared in relation to occupied men, where the approach is of a gender perspective. So, it was used the Space Data Exploratory Analysis (AEDE) technique, by the Moran s I statistics and by the clusters identification analysis. Moran s I statistics allowed to evaluate the existent correlation between a region and their neighbors considering a variable. However the clusters identification analysis allowed a simple visualization of next regions conglomerate in a map that pursue similar values, in other words, allow the clusters visualization. The analyzed period was the year 2006, by the data of 2006 Agriculture Census, performed by the Statistics and Geography Brazilian Institute IBGE, these data were studied by an absolute form and rates. The AEDE revealed the occupied women distribution among the states of Paraná, Santa Catarina and Rio Grande do Sul. The results, to the scholarity in the absolute data or by rates, presented relation with the number of occupied women, in this case, where it presented a number of occupied men with a greater scholarity. In the activities out of the establishments, was also verified that in cities with the lesser occupation per woman, the greater was the number of cities the women followed any activity outside the property. With the results were found positive spatial autocorrelation of the absolutely occupied women in the Southern Brazil rural area, showing off that spatial localization interferes in women s values. Having a contribution to gender perspective analysis in Southern Brazil and allowing new researches or concepts for the study, where the data revealed a proportion of about 40% of the occupied women from the total in the Southern Brazil agriculture.